(untitled) (LEARNing Landscapes, 2016)
At a start-up urban magnet middle school, we are committed to a student-centered inquiry-based learning environment that values extended project-based learning. In order to make projects relevant, we work with community members to harness their expertise in the design, execution, and evaluation of student work. We recognize that partnerships that allow community members to showcase their own talents, skills, and knowledge forge meaningful relationships that enhance student learning.